Clinical use of 3D printed models for anterior communicating artery aneurysm clipping: a prospective cohort study - Feng, Chudi; Wang, Jianli; Lv, Keqiong; Dong, Changming; Li, Jinquan; Zhao, Li; Duan, Ying; Shao, Honghong; Yuan, Zigang (Frontiers in Surgery, 2025)
ObjectiveThe complex anatomy of anterior communicating artery aneurysms (ACoA) makes microsurgical clipping challenging. This study assessed the clinical value of 3D printed models based on digital subtraction angiography (DSA) in the surgical management of ACoA aneurysms, with a comprehensive analysis of ruptured and unruptured cases.MethodsA prospective cohort study was conducted from 2022 to 2023, involving 60 patients with ACoA aneurysms. The study included both ruptured (n = 42) and unruptured (n = 18) aneurysms. Patients were divided into two groups: a control group (n = 30) using traditional 2D DSA imaging and 3D rotational angiography displays and a model group (n = 30) utilizing 3D printed models. Patient characteristics, including comorbidities such as hypertension, smoking status, and diabetes, as well as Hunt and Hess scores for ruptured cases, were recorded. For ruptured cases, Fisher grades, Hunt and Hess scores, and presence of hydrocephalus were documented. Primary outcomes included residual aneurysm neck, parent artery stenosis, and modified Rankin Scale (mRS) at 14 days post-surgery. Secondary outcomes encompassed intraoperative complications, diagnostic accuracy, operative duration, and perioperative clinical parameters. Temporary clip usage and duration were recorded, and intraoperative vessel patency was verified using Doppler ultrasonography and indocyanine green video angiography.ResultsAt 14 days postoperatively, the model group demonstrated significantly lower rates of residual aneurysm neck (0% vs. 20%, p = 0.012) and parent artery stenosis (3.33% vs. 23.33%, p = 0.026). Fewer patients in the model group had mRS ≥ 3 (10% vs. 33.33%, p = 0.028). Intraoperative complications were reduced in the 3D model group (6.67% vs. 26.67%, p = 0.038), with significantly shorter operation duration (264.47 ± 52.27 vs. 313.10 ± 59.90 min, p = 0.001). The model group had higher preoperative diagnostic accuracy (93.33% vs. 70%, p = 0.02) With the aid of 3D models, surgical precision and outcomes are improved.Conclusion3D printed models derived from DSA imaging significantly enhance the surgical management of ACoA aneurysms, offering improved diagnostic accuracy, reduced complications, and better functional outcomes. The average production time of 2–8 h and cost of approximately 120 USD per model make this approach feasible even for time-sensitive cases. These findings highlight the potential of patient-specific 3D models as a valuable adjunct in the management of complex ACoA aneurysms.